Response of Masonry-Infilled Reinforced Concrete Frames Strengthened at Interfaces with Geo-Fabric under In-Plane Loads - K. S. Sreekeshava; Hugo Rodrigues; A. S. Arunkumar (Buildings, 2023)
The interfaces between masonry infill and reinforced concrete (MI-RC) frames are identified as the weakest regions under lateral loads. Hence, the behavior of such frames under lateral loads can be understood mainly through experimental investigations. The deformation demands induced by horizontal loads on RC frames with infill masonry walls change due to contact losses between the infill masonry and the RC frames. This can be controlled by providing proper reinforcements at the interfaces. In the present experimental investigation, three half-scaled models subjected to reversed cyclic lateral in-plane loads were tested. In detail, the specimens considered are the MI-RC frame model, an MI-RC frame with geo-fabric reinforcement at the interface and an MI-RC frame with geo-fabric reinforcement at interfaces with an open ground story. The models were subjected to reversed cyclic lateral in-plane loads, and the post-yield responses of the models with respect to stiffness degradation, drift, energy dissipation, ductility and failure mode have been discussed.